ANALISIS FRAMING PEMBERITAAN MEDIA CETAK LOKAL DALAM ISU GENDER DI YOGYAKARTA TAHUN 2013 - , FITA PURWANTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The gender concept is still have to do some adaptations as a local value system, the mass media tend to have strategic position to make a change in society. Paradox happened when the news which they produce is still gender biased. The patriarch ideology as a society mainstream ideology in Indonesia, bring consequences to womenâs role and position in the mass media, however, the media does not live in value free-condition towards its social environment. This fact is absolutely contradictive with the normative idea emerge on UU Pers No. 4/Tahun 1999 tentang Asas, Fungsi, Hak, Kewajiban dan Peranan Pers dan Kode etik Jurnalistik Pasal 1. This framing analysis research is try to give decsription about news framing related to gender issues that published by the local print media in Yogyakarta, Kedaulatan Rakyat and Harian Jogja. From the collected data, this research put on desription that the news reconstruction from SKH Kedaulatan Rakyat bring the voice of gender issues concerned-side, meanwhile the news reconstruction from Harian Jogja tend to deliver the voice of civil society. Harian Jogja used source as a scapegoat to discredit and give certain label to women. Kedaulatan Rakyatâs news decription stressed on women roles and eliminating violence againts women. Whereas, Harian Jogjaâs news is more describing sensuality. Harian Jogja put woman journalist/editor more in gender issue, but it did not guarantee its news would be gender sensitive. News framing related to gender issue on Kedaulatan Rakyat give appreciation to women, while Harian Jogjaâs news is not give the same yet.